2012
DOI: 10.1021/jp303609h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Induced Structural Changes of Bovine Serum Albumin in Aqueous Media: A Detailed Physicochemical and Spectroscopic Study

Abstract: Structural changes of a globular protein, bovine serum albumin (BSA), as a consequence of interaction with the surface active ionic liquids (ILs)-3-methyl-1-octylimidazolium chloride, [C(8)mim][Cl], and 1-butyl-3-methylimidazolium octylsulfate, [C(4)mim][C(8)OSO(3)]-have been investigated using various physicochemical and spectroscopic techniques such as tensiometry, conductometry, steady-state fluorescence, far-UV circular dichroism spectroscopy (CD), and dynamic light scattering (DLS). The interactional beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 67 publications
7
121
1
1
Order By: Relevance
“…The smaller increase in D h from ≈ 8.0 nm to ≈ 11.0 nm in case of BSA-ILS-1 system is assigned to the monomeric interaction of ILS with BSA via electrostatic and hydrophobic interactions leading to partial unfolding of its secondary structure forming ILS-1-MCs. Such marginal increase in D h due to unfolding in monomeric concentration regime has also been reported for other imidazolium based ILSs bearing simple alkyl chain as well as for conventional surfactants 18,33,34. However, in case of BSA-ILS-2 and BSA-ILS-3 systems, a substantial increase in D h from ≈8 nm to 126 nm, and to ≈207 nm, respectively via intermediate structures having D h ≈40 nm up to C 1 is observed.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The smaller increase in D h from ≈ 8.0 nm to ≈ 11.0 nm in case of BSA-ILS-1 system is assigned to the monomeric interaction of ILS with BSA via electrostatic and hydrophobic interactions leading to partial unfolding of its secondary structure forming ILS-1-MCs. Such marginal increase in D h due to unfolding in monomeric concentration regime has also been reported for other imidazolium based ILSs bearing simple alkyl chain as well as for conventional surfactants 18,33,34. However, in case of BSA-ILS-2 and BSA-ILS-3 systems, a substantial increase in D h from ≈8 nm to 126 nm, and to ≈207 nm, respectively via intermediate structures having D h ≈40 nm up to C 1 is observed.…”
supporting
confidence: 71%
“…From Figure S2B (supporting information), it has been found that N for different ILSs is 57 (ILS-1), 76 (ILS- based ILSs. 33,34 The increase in hydrophobic interactions between alkyl chains of ILSs forming hemi-micelles lead to decrease in interactions between BSA and ILSs stabilizing the ACs between C 2 and C 3 . This destabilizes the ACs leading to structural changes.…”
Section: Results Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trp 134 present at the surface of the protein in domain I is surrounded by a number of negatively charged aspartic (Asp) and glutamic (Glu) acid residues to which the cationic gemini (C 12 Cys) 2 can bind by electrostatic interactions thus perturbing the native conformation of BSA [60]. The observed changes suggest a shift of the fluorophores to a more hydrophobic environment that can be attributed to internalization of the fluorophore towards the protein hydrophobic core due to protein refolding (which is possible when protein gets stabilized [59,61]) or to hydrophobic interactions between the dodecyl chains of (C 12 Cys) 2 and hydrophobic amino acid residues around Trp 134, such as leucine (Leu), Tyr and Phe [60], leading to a decrease in intrinsic fluorescence intensity [26,28,57,62,63]. For surfactant concentrations above the CAC (0.30 g L −1 ) the blue shift vanishes and the intensity of the emission reaches a constant value at a surfactant concentration of 0.70 g L −1 .…”
Section: Fluorescence Emission and Uv-vis Absorption Spectramentioning
confidence: 99%
“…The fluorescence quenching process can be described by the Stern-Volmer equation [26,27,50,58,61,66]:…”
Section: Fluorescence Quenching Datamentioning
confidence: 99%